1990
DOI: 10.1111/j.1365-2141.1990.tb07887.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trial with the oral iron chelator 1,2‐dimethyl‐3‐hydroxypyrid‐4‐one (L1) I. IRON CHELATION AND METABOLIC STUDIES

Abstract: A long-term clinical trial of 1-15 months has been carried out with the oral iron chelator 1,2-dimethyl-3-hydroxypyrid-4-one (L1) in 13 transfusion-dependent iron-loaded patients. Urinary iron excretion was greatest in patients with thalassaemia major and was related to the number of previous transfusions but not to the serum ferritin level. Substantial increases of urinary iron were observed in all the patients when the frequency of the daily dose was doubled and in response to 2 x 3 g L1 daily 11 of 12 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 15 publications
1
58
0
1
Order By: Relevance
“…14,34 Although one study reported fecal iron excretion with deferiprone ingestion to be 15% to 23% of total excretion, 34 other studies, either published or in abstract form, showed no increase or only negligible increase in fecal iron excretion and no detectable deferiprone in feces. 12,35,36 Metabolic balance studies in 13 patients showed that the level of total iron excretion in response to deferiprone (75 mg/kg) was 62% (range, 24%-129%) of that achieved with deferoxamine (60 mg/kg over 8 hours subcutaneously). 35 Although all patients were in net negative balance when treated with deferoxamine, only 6 of 13 were in net negative balance as a result of taking deferiprone.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,34 Although one study reported fecal iron excretion with deferiprone ingestion to be 15% to 23% of total excretion, 34 other studies, either published or in abstract form, showed no increase or only negligible increase in fecal iron excretion and no detectable deferiprone in feces. 12,35,36 Metabolic balance studies in 13 patients showed that the level of total iron excretion in response to deferiprone (75 mg/kg) was 62% (range, 24%-129%) of that achieved with deferoxamine (60 mg/kg over 8 hours subcutaneously). 35 Although all patients were in net negative balance when treated with deferoxamine, only 6 of 13 were in net negative balance as a result of taking deferiprone.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Several groups subsequently confirmed in longer term studies that deferiprone was an orally active iron chelator, [11][12][13][14][15] and substantial data concerning the efficacy and toxicity of deferiprone have accumulated over 15 years. The results of these trials and of animal and cell culture studies have been extensively reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…The above study suggests that the iron mobilised by L1 in individuals with normal body iron store levels including focal iron deposits in FA patients could be redistributed in the body via transferrin instead of being excreted. Measurement of urinary iron excretions have shown that usually only about 1-3 mg iron can be excreted by normal individuals of about 75 kg body weight, per a 3 g dose of L1 [67,[124][125][126] . In comparison, in iron loaded TM patients of approximately the same body weight, substantial increases in iron excretion of up to 71.5 mg can be observed by using the same dose of L1 [67,[123][124][125][126] .…”
Section: The Role Of Deferiprone In the Treatment Of Friedreich Ataxiamentioning
confidence: 99%
“…Measurement of urinary iron excretions have shown that usually only about 1-3 mg iron can be excreted by normal individuals of about 75 kg body weight, per a 3 g dose of L1 [67,[124][125][126] . In comparison, in iron loaded TM patients of approximately the same body weight, substantial increases in iron excretion of up to 71.5 mg can be observed by using the same dose of L1 [67,[123][124][125][126] . Despite that the net amount of iron excreted by L1 in normal individuals is small, continuous administration over prolonged periods of many months and years may cause iron deficiency, unless iron can be replaced from dietary sources or from iron supplements [64,123] .…”
Section: The Role Of Deferiprone In the Treatment Of Friedreich Ataxiamentioning
confidence: 99%
“…Topical CP94 administration has been investigated in humans as way of improving PpIX-induced PDT for the treatment of certain non-melanoma skin cancers and precancers. Dose escalating pilot studies in nodular basal cell carcinoma (one treatment cycle without lesion debulking) with simultaneous topical ALA [26] or MAL administration [27] have already been conducted and determined that CP94 administration was a safe, effective and feasible treatment modification which did not produce any additional adverse reactions.…”
Section: Introductionmentioning
confidence: 99%